2013
DOI: 10.1159/000343753
|View full text |Cite
|
Sign up to set email alerts
|

EBNA-2-Deleted Epstein-Barr Virus from P3HR-1 Can Infect Rabbits with Lower Efficiency than Prototype Epstein-Barr Virus from B95-8

Abstract: Objectives: To clarify characteristics on rabbit in vivo infection with type 2 EBV nuclear antigen (EBNA-2)-deleted Epstein-Barr virus (P3HR-1-EBV) and compare infectious efficacy of P3HR-1-EBV with previously reported prototype type 1 EBV from B95-8. Methods: Twelve Japanese White rabbits were inoculated with P3HR-1-EBV via intranasal or intravenous routes and autopsied on day 70–84. Results: In only 2 of 12 P3HR-1-EBV-inoculated rabbits, EBV-DNA was detected in peripheral blood mononuclear cells (PBMCs). Bam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Although B-95-8 is a very commonly used source of EBV, it is important to assess if the rabbits are equally susceptible to infection with other strains of the virus. A previous study reported that rabbits were susceptible to P3HR1 stain [ 65 ]. However, this strain lacks EBNA2 and is, therefore, not a bona fide representative of wild-type virus infecting humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although B-95-8 is a very commonly used source of EBV, it is important to assess if the rabbits are equally susceptible to infection with other strains of the virus. A previous study reported that rabbits were susceptible to P3HR1 stain [ 65 ]. However, this strain lacks EBNA2 and is, therefore, not a bona fide representative of wild-type virus infecting humans.…”
Section: Discussionmentioning
confidence: 99%
“…The EBV DNA persistence in the spleen as revealed by the presence of EBER-positive lymphocytes, LMP1, EBNA2 and ZEBRA mRNAs occurred in a proportion of rabbits resulting from intravenous inoculation with a very high virus load [13]. It seems that both the route of virus administration as well as the source of the inoculated virus might be essential for its further spread and for the efficiency of elimination of the persisting (or latent) virus genome [38,39,40]. Summing up, the EBV DNA in our rabbits was present in a smaller proportion of B lymphocytes along with simultaneous expression of LMP1 antigen and the absence of EBNA-1 antibody.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with previous experiments showing that EBNA2 is essential in B-cell transformation [ 47 ]. However, in vivo experiments indicate that EBNA2 deletion does not preclude the establishment of infection [ 48 ] or development of cancer [ 49 ]. Notably, EBNA2 expression is highly efficient; experiments have shown that a single detectable EBV genome is sufficient to drive EBNA2 expression [ 50 ].…”
Section: Ebv Latencymentioning
confidence: 99%